Hemostatic profile of infants with spontaneous prematurity: can we predict intraventricular hemorrhage development? - Audrey Hochart; Alexandra Nuytten; Adeline Pierache; Anne Bauters; Antoine Rauch; Bénédicte Wibaut; Sophie Susen; Jenny Goudemand (BMC, 2019)
Abstract Background Defining hemostatic profile for preterm infants is a challenge when severe bleedings are frequent. Methods The aim was to define the hemostatic profile at birth of infants with spontaneous prematurity and to evaluate whether characteristic profiles can predict the development of intraventricular hemorrhage (IVH) in prematures. Results We included 122 newborns with a median age of 315/7 gestational age (GA) [292/7;340/7] and median weight of 1145 g [785;1490]. Levels of fibrinogen, factor II (FII) and factor V (FV) rose with GA (p = 0.017,p = 0.009, p = 0.001). In the group of 230/7 - 286/7 GA, the 5th percentile was defined as 0.6 g/L for fibrinogen, 15 IU/dL for FII and 16 IU/dL for factor V (n = 30). In the group of 290/7-326/7 GA, the 5th percentile was defined as 1.0 g/L for fibrinogen, 24 IU/dL for FII and 41 IU/dL for factor V (n = 46). In the group of 330/7-366/7 GA, the 5th percentile was defined as 1.0 g/L for fibrinogen, 24 IU/dL for FII and 30 IU/dL for factor V (n = 46). Level of fibrinogen was higher in case of vaginal delivery and lower in case of IUGR. Only lower level of FV at birth was significantly associated with IVH (63.5 [46.0; 76.5] vs 74.0 [58.0; 89.0], p = 0.026) with an unadjusted OR per SD increase in FV of 0.57 (95%CI, 0.34 to 0.96). After adjustment for age, the association between FV level and IVH was slightly attenuated (adjusted OR, 0.70; 95%CI, 0.40 to 1.23) but remained not significant (p = 0.22).There was no correlation with FII and fibrinogen. Conclusions We can define hemostastic profile of prematures and corroborate references ranges for studied parameters. Further large studies are still called for, to correlate the grade of hemorrhage and the factor V level at birth.